Representasi Konflik Batin dan Identitas Diri dalam Tokoh Haia Novel Laut Tengah Melalui Pendekatan Psikologi Sastra Sigmund Freund - Laili Ramadhani; Ahmad Ilzamul Hikam; Irfani Husnawiyah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This article analyzes the representation of inner conflict and the search for self-identity in the character Haia in the novel Laut Tengah by Berliana Kimberly, using Sigmund Freud's literary psychology approach. This approach highlights the dynamics of the interaction between the id, ego, and superego in shaping Haia's personality and behavior. Through this analysis, it is found that Haia experiences deep inner conflict due to the tension between personal drives and social demands. The ego defense mechanisms used by Haia, such as rationalization and sublimation, play an important role in maintaining her psychological balance. In addition, the social and cultural environment also influences the formation of Haia's self-identity, creating a dilemma between fulfilling external expectations and pursuing personal happiness. Haia's identity transformation process reflects the search for meaning and self-acceptance that are essential in achieving psychological balance. The implications of this analysis suggest that literature can function as a mirror of life, reflecting the psychological dynamics experienced by individuals in society.